Detection of chlamydia trachomatis by immunological methods in adult and adolescent female population in Cuiabá, Mato Grosso - Machado, Alexandre Paulo; Matos, Marly Pinto de; Zavala, Arturo Ayala Zavala y; Silva, Zaíra Batista da; Barbosa, Dulce Aparecida (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Worldwide, Chlamydia trachomatis infection remains a major public health problem, especially for sexually active young adults. Objective: To investigate the sexually transmitted disease by Chlamydia trachomatis in adolescents and young women aged 15–25 years from Cuiabá and Várzea Grande, Mato Grosso, Brazil, through the ELISA and direct immunofluorescence methods. Methods: A cross-sectional quantitative study of endocervical samples from 328 nonpregnant, sexually active women who received care in basic health units. Endocervical samples were collected and C. trachomatis antigens detected by ELISA and direct immunofluorescence methods. Results: A total of 11 positive samples were obtained with ELISA (3.4%) and 69 with direct immunofluorescence (24.4%). The largest number of cases occurred in the 16–25 years age group (24.39%). Conclusion: The rate of positive cases observed was representative, similarly to those found in other studies, and, therefore, indicating Chlamydia strains circulating in the population studied. Amplification of prophylactic, diagnostic, and therapeutic measures in public health services will be an important step to counter the spread of sexually transmitted diseases, including genital infection by C. trachomatis in the female population.